Entrepreneurship and innovation an economic approach - McDaniel, Bruce A. 1946- (Routledge, 2015)
"The book provides in-depth discussion of several critical concepts: the economic development of a product; Schumpeter's "temporary monopoly control;" the economic bounds of product and process innovations; and changing production functions. It also develops and integrates an analysis of how innovation-induced modifications in either products or processes affect both short-run and long-run average costs in production"--Provided by publisher.